Development and increase of efficiency of transport and logistic infrastructure (Journal of Economic Research & Business Administration, 2018)
In the Address, the President of the Republic of Kazakhstan noted seven key clusters determining the long-term specialization of the economy in non-resource sectors. Among them, the development and increase of the efficiency of transport and logistics infrastructure was noted. The purpose of the study is to develop transport logistics, the development of transport and logistics centers in Kazakhstan, the provision of a range of logistics services based on outsourcing.To develop and apply innovations in the field of transport and logistics. Introducing the components of an intelligent transport system that will effectivelymanage the transport flows and determine the needs for further development of the infrastructure.The theoretical and methodological basis of the study was the works of domestic and foreign scientists,materials of scientific and practical conferences, information resources of the Internet.The methodologicalbasis of the research is – methods of system and economic analysis, statistical data processing.Theauthors consider the composition of the transport infrastructure of the Republic of Kazakhstan.The signsinherent in the transport and logistics infrastructure in the current conditions of the country’s developmentare given.Logistic services are provided, so-called logistic intermediaries. Are given experience oftransport and logistics centers of foreign countries.The article considers the necessity of functioning andcreation of modern logistics centers in the Republic of Kazakhstan.Digital technologies are proposed inthe field of transport and logistics, which will increase the volume of transit traffic in the country, increasethe transport flow of the country, reduce the number of injured as a result of road accidents, increase thestate budget through which of Kazakhstan